Players’ On-Court Movements and Contextual Variables in Badminton World Championship - Valldecabres, Raúl; Casal, Claudio A.; Chiminazzo, João Guilherme Cren; de Benito, Ana María (Frontiers in Psychology, 2020)
This study aimed to analyze the elite badminton players’ on-court movements related to contextual variables (game, round, and match status). A total of 18 matches of the Jakarta 2015 World Championship (1,273 points and 5,710 play actions) were examined by univariate and bivariate analyses. Significant differences were found when comparing the players’ on-court movements related to game, round, and match status (p < 0.05). All movements were executed more frequently in game 2, with the exception of diagonal large backward left (DLBL), diagonal short backward left (DSBL), diagonal short backward right (DSBR), and longitudinal short backward (LSB). The results obtained related to the round showed that longitudinal large backward (LLB) was the most frequent footwork in R1/16 and R1/2, diagonal short forward left (DSFL) was the most frequent one for R1/4, and transversal short right (TSR) was the most used movement for the final round. According to match status, no movement (NM) was the most common situation before hitting the shuttlecock at any moment during the match. This study shows how contextual variables modulate the elite players’ on-court movements. This information could be valuable for coaches and players, allowing them to better understand the players’ behavior in a competition, which could be used to design more specific training tasks and prepare match strategies in order to improve the players’ performance in competitions.